Exploring factors influencing the consistent adoption of a post-stroke upper extremity outcome measure using Normalisation Process Theory - Silvana X. Choo; Joshua Yong; Shaikh Abdullah Bin Mohamed Rafi; Chen Ju Lo; Jun Bin Tong; Elaine Lum; Julian Thumboo (BMC Health Services Research)
Abstract Background Stroke rehabilitation guidelines recommend using outcome measures like the Fugl-Meyer Assessment for Upper Extremity (FMA-UE) to assess post-stroke upper extremity function. However, integrating such outcome measures into routine clinical practice remains challenging, highlighting the need to understand factors affecting their implementation in evolving healthcare models. Objective Our study aimed to identify the barriers and facilitators to sustain the routine use of the FMA-UE among hospital-based occupational therapists (OTs) using a theory-driven approach. Methods Employing a mixed-method sequential exploratory study design rooted in Normalisation Process Theory (NPT), we gathered quantitative data through a validated survey followed by qualitative insights analysed with directed content analysis from focus group discussions involving occupational therapists from four hospitals. Results Survey findings (n = 34) revealed barriers primarily associated with NPT constructs of collective action and coherence. Facilitators were linked to the cognitive participation construct. Key barriers identified in focus groups included insufficient coaching, competing priorities, and perceived limited value of the FMA-UE. Facilitators included legitimation of therapists’ role in outcome measurements and an open learning culture. Conclusions Through a theory-based approach, we identified barriers and facilitators to sustain the routine of the FMA-UE. Our findings offer insights for designing implementation strategies to embed the FMA-UE into routine practice, supporting its sustained use in stroke rehabilitation.